LA TRANSFORMADA DE LAPLACE EN LA SOLUCIÓN DE ECUACIONES DIFERENCIALES CON ALGORITMO DE CÁLCULO EN MATHCAD - JUAN ANTONIO MARTIN ALFONSO; CARLOS MANUEL MATA RODRÍGUEZ (Revista Ingeniería, Matemáticas y Ciencias de la Información, 2019)
In the history of Mathematics, frequently happens that certain topics (especially the numeric calculation) has perfectlydefined its theoretical solution, but the heap of operations to find a conclusive result, in multiple occasions, don’t allowto arrive to the final results.